The PLGF/c‐MYC/miR‐19a axis promotes metastasis and stemness in gallbladder cancer. Issue 5 (27th April 2018) - Li, Huaifeng; Jin, Yunpeng; Hu, Yunping; Jiang, Lin; Liu, Fatao; Zhang, Yijian; Hao, Yajuan; Chen, Shili; Wu, Xiangsong; Liu, Yingbin
Abstract : Gallbladder cancer (GBC) is the most common malignant tumor of the biliary tract system. Epithelial–mesenchymal transition (EMT) plays a vital role in the process of tumor metastasis. Mesenchymal‐like cells can serve as a source of cancer stem cells, which can confer the EMT phenotype. Placental growth factor (PLGF) belongs to the vascular endothelial growth factor family and plays a vital role in cancer. However, the underlying molecular mechanisms about the influence of PLGF on EMT in GBC remain unknown. Here we show that PLGF expression levels were higher in GBC tissues than in normal adjacent tissues and were associated with poor prognosis in GBC patients. Exogenous PLGF enhanced the migration, invasion, and tumorsphere formation of GBC cells. Conversely, knockdown of PLGF decreased the aggressive phenotype of GBC cells. Mechanistically, exogenous PLGF upregulated microRNA‐19a (miR‐19a) expression through the activation of c‐MYC. Moreover, Spearman's correlation analysis showed a positive pairwise correlation among PLGF, c‐MYC, and miR‐19a expression in GBC tissues. Taken together, these results suggest that PLGF promotes EMT and tumorsphere formation through inducing miR‐19a expression by upregulating c‐MYC. Thus, PLGF could be a promising molecular therapeutic target for GBC. Abstract : PLGF enhanced the migration, invasion and tumorsphere formation of GBC cells through inducing miR‐19a expression by upregulating c‐MYC. Thus, PLGF may be a promising molecular therapeutic target for GBC.